Perceived Factors Influencing Lactation and Exclusive Breastfeeding among Nursing Mothers (2016)
Background: Maternal mortality has been an issue of concern in developing countries of which Nigeria is one. These deaths are preventable if the health facilities are utilized, births are attended by skilled health providers and complications attended to promptly. Statistics have shown that, though over fifty percent of women attend ANC but less than forty percent are delivered by a skilled birth attendant. Objective or Aims: This study ascertains the factors influencing the choice of health care provider by women during childbirth in Ibadan, Oyo state Nigeria. Methodology: A descriptive design was used to elicit information from mothers attending postnatal and immunization clinics of selected hospitals. All the women attending the clinics were selected. Self-administered questionnaire was used to obtain information and the data collected were analyzed using percentage, frequency and chi square test. Results: The results of the study revealed that 76.9% of the women identified midwives as the most skilled for delivery but only 43.6% are being delivered by midwives. Over, 60% had poor perception and negative attitude towards the midwives. Some of the factors identified to influence delivery from a TBA are ignorance, lack of alternative, accessibility, lesser time consumption and availability. Income of women and satisfaction with services provided does not have significant association with the choice of health care provider (p= 0.180) but age was significantly associated with choice of Provider (p=0.017). Conclusions: Community based awareness, education and counselling, alongside improving midwives’ interpersonal skill with effective collaboration, monitoring and supervision of both TBAs and midwives will enhance good choices.